2003
DOI: 10.1046/j.1440-1843.2003.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous and pulmonary sarcoidosis in a Hong Kong Chinese woman with silicone breast prostheses

Abstract: Sarcoidosis is rarely reported in Hong Kong. We report cutaneous and pulmonary sarcoidosis in a 54-year-old Chinese woman, who presented with papular lesions over the face and neck. She had silicone breast augmentation surgery 4 years earlier. Skin biopsy revealed granulomatous inflammation and anti-tuberculosis treatment was started empirically but stopped 2 months later owing to a poor response. A right supraclavicular lymph node was aspirated and revealed granulomatous inflammation. The CXR was normal initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Another possible cause of cutaneous and pulmonary sarcoidosis was reported by Chang et al [37] who found granulomatous formation in papular skin lesions, superficial lymph nodes and in transbronchial biopsies in a middle-aged Chinese females who had silicone breast augmentation a few years earlier. They speculate that silicone elastomer from the implants may have leaked and caused the granulomatous reaction.…”
Section: Other Types Of Skin Lesionsmentioning
confidence: 85%
“…Another possible cause of cutaneous and pulmonary sarcoidosis was reported by Chang et al [37] who found granulomatous formation in papular skin lesions, superficial lymph nodes and in transbronchial biopsies in a middle-aged Chinese females who had silicone breast augmentation a few years earlier. They speculate that silicone elastomer from the implants may have leaked and caused the granulomatous reaction.…”
Section: Other Types Of Skin Lesionsmentioning
confidence: 85%
“…193 The adjuvants associated with ASIAs include silicone, hyaluronic acid, 196 and mineral oil. 197 Several sarcoidosis-like reactions related to ASIAs have been reported after silicone breast implantation, [198][199][200][201] with resolution of the sarcoidosislike reaction after removal of the implant. 202 Multisystem granulomatous reactions related to ASIAs should be differentiated from local foreign body granulomatous reactions (eg, siliconomas).…”
Section: Implant-and Device-induced Sarcoid-like Reactionsmentioning
confidence: 99%
“…Silicone migration may follow these paths, but it may also spread retrogradally or along other pathways (14). Rare cases of pneumonitis have also been observed (15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%